Report on Improved Agricultural Implements in Himachal Pradesh - Planning Commission (Planning Commission, Government of India, 1967)
The Report on Improved Agricultural Implements in Himachal Pradesh examines the early-stage development of farm mechanization in the state, highlighting constraints in research, manufacturing, training, and distribution of modern agricultural tools. The study identifies the absence of local production facilities, limited artisan training, inadequate credit access, and weak extension services as major barriers to adoption. Given the state’s diverse agro-climatic and hilly terrain, the report emphasizes the need for location-specific implements supported by field trials and demonstration programs. Key recommendations include strengthening research and training centers, promoting private and cooperative manufacturing, enhancing repair and maintenance capacity through artisan training, streamlining supply chains, and improving financial support to farmers. Overall, the report outlines a structured strategy to modernize agricultural practices in Himachal Pradesh through localized solutions, institutional support, and effective extension mechanisms.
Agriculture Team Committee on Plan Projects Planning Commission New Delhi April 1966
Agriculture Team Committee on Plan Projects Planning Commission New Delhi April 1966
Keywords: Agricultural Implements; Himachal Pradesh Agriculture; Farm Mechanization; Research and Training Facilities; Local Manufacturing; Extension Services; Private Sector Participation; Artisan Training; Credit Facilities; Distribution Systems; Demonstration Farms; Agro-Climatic Adaptation